The impact of dapagliflozin on FIB-4 index over 2 years in patients with type 2 diabetes mellitus - Özkan, Semra; Gezer, Deniz (The European Research Journal, 2025)
Objectives: Dapagliflozin belongs to the sodium-glucose co-transporter 2 inhibitor drug group used in the treatment of type 2 diabetes. This study aimed to investigate the effects of dapagliflozin and simultaneous dapagliflozin+pioglitazone therapy on the FIB-4 index, associated with liver inflammation and fibrosis, at the end of the first and second years. Methods: This retrospective study, conducted between 01.01.2017 and 01.01.2020, included 386 patients using dapagliflozin alone (DAPA Group) and 122 patients using dapagliflozin in combination with pioglitazone (DAPA+PIO Group). ALT, AST, and FIB-4 index were compared at baseline, at week 52, and at week 104. Results: The DAPA group consisted of 243 females (63%) and 143 males (37%) with a mean age of 59.8±6 years. The DAPA+PIO group consisted of 61 females (50%) and 61 males (50%) with a mean age of 58.3±5 years. No significant differences were observed between the groups in ALT, AST, hemoglobin levels, and platelet counts at the baseline, at the 52nd week, and at the 104th week (P>0.05). Statistically significant decreases in fasting blood glucose and HbA1C levels were observed in both groups at baseline, week 52, and week 104 (P<0.001). Furthermore, both groups exhibited no statistically significant changes in the FIB-4 index during the first and second years compared to baseline (P>0.05). Conclusions: Dapagliflozin, either alone or in combination with pioglitazone, did not alter the FIB-4 index associated with liver fibrosis and inflammation over 1 and 2 years in patients with type 2 diabetes. Despite experimental evidence indicating its potential to reduce liver fibrosis, clinical data remain inconclusive. Future prospective studies with longer durations are necessary for a clearer understanding.